Effects of noble metals doped on mesoporous LaAlNi mixed oxide catalyst and identification of carbon deposit for reforming CH4 with CO2. Issue 3 (4th July 2013) - Arandiyan, Hamidreza; Peng, Yue; Liu, Caixia; Chang, Huazhen; Li, Junhua
Abstract BACKGROUND The effect of the B cation on the surface properties and catalytic activity in the dry reforming reaction over La0.4M0.6Al0.2Ni0.8O3 (M=noble metal) perovskite‐type oxides with surface area 3.26–4.14 m2 g–1 and rhombohedral structure was studied. RESULTS Among LaAlxNi1‐xO3 series, LaAl0.2Ni0.8O3 had the highest catalytic activity, but suffered a slow deactivation with time‐on‐stream (TOS). It is observed that all samples presented similar activity at low reaction temperatures (500–600°C), while at higher temperatures (600–850°C) the prepared solid was more active and perovskite phase was transformed into Ni0 or La2O2CO3. It was found that among the noble metal samples, La0.4Rh0.6Al0.2Ni0.8O3 possessed the highest surface area and surface oxygen concentration and the best low‐temperature reducibility. For the Rh catalyst the CH4 and CO2 conversions were 89.1 and 86.2%, which were the most resistant against coke deposition and showed very high stability without decrease in reforming and remained constant during the 3000 min TOS. The following order of activity was observed: La0.4Rh0.6Al0.2Ni0.8O3 > La0.4Ru0.6Al0.2Ni0.8O3 > LaAl0.2Ni0.8O3> La0.4Ir0.6Al0.2Ni0.8O3 ≥La0.4Pt0.6Al0.2Ni0.8O3 > La0.4Pd0.6Al0.2Ni0.8O3. CONCLUSIONS It is believed that the high surface area and surface oxygen concentration and good low‐temperature reducibility were responsible for the good catalytic performance of the La0.4Rh0.6Al0.2Ni0.8O3 sample. © 2013 Society of Chemical Industry